2022
DOI: 10.1088/1361-6595/ac5eca
|View full text |Cite
|
Sign up to set email alerts
|

On the use of ultra-high resolution PIC methods to unveil microscale effects of plasma kinetic instabilities: electron trapping and release by electrostatic tidal effect

Abstract: Ultra-high resolution Particle-in-Cell coupled to Monte-Carlo collisions modelling unveils microscale instabilities in non-equilibrium plasmas fulfilling Penrose's instability criterion. The spontaneous development of ion turbulence in the phase-space generated by charge exchange collisions leads to finite amplitude modulations of the local electric field. The latter are responsible for the trapping of low energy electrons and their transport from the plasma volume to the sheath vicinity. Electrostatic tidal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Note that in recent years, hybrid models of gas-discharge plasma have gained great popularity, in which heavy particles (ions, excited particles, neutrals) are described by the fluid approximation equations, and electrons by the PIC/MCC method [34][35][36][37][44][45][46][47][48][49][50][51][52][53]. The idea of this method is as follows: the trajectory of an electron starting from the cathode is calculated according to the equations of motion mechanics in a given electric field; in this case, the elastic and inelastic scattering of an electron is taken into account as a random process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that in recent years, hybrid models of gas-discharge plasma have gained great popularity, in which heavy particles (ions, excited particles, neutrals) are described by the fluid approximation equations, and electrons by the PIC/MCC method [34][35][36][37][44][45][46][47][48][49][50][51][52][53]. The idea of this method is as follows: the trajectory of an electron starting from the cathode is calculated according to the equations of motion mechanics in a given electric field; in this case, the elastic and inelastic scattering of an electron is taken into account as a random process.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of such numerical solutions, the empirical distribution of the ionization source is determined and the system of fluid equations for electrons and ions is closed. Despite the success of numerical calculations [34][35][36][37][44][45][46][47][48][49][50][51][52][53], such models are often limited by computational resources and do not allow taking into account the completeness of the processes occurring in a nonequilibrium plasma: a large number of elementary processes, gas heating, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, charge-exchange collisions may give rise to potential perturbations and energy losses of positive ions when colliding with neutrals, causing the Ion Velocity Distribution Function (IVDF) to become linearly unstable 11 . From this point of view, a self-consistent numerical analysis by Schiesko et al 12 showed that the ion-acoustic instability was triggered by a non-monotonically decreasing ion’s VDF (i.e., satisfying Penrose’s criterion 13 ) inducing potential modulations. Furthermore, as demonstrated by the convective nature of this instability, no net damping was observed for the chosen parameters 12 .…”
mentioning
confidence: 99%
“…From this point of view, a self-consistent numerical analysis by Schiesko et al 12 showed that the ion-acoustic instability was triggered by a non-monotonically decreasing ion’s VDF (i.e., satisfying Penrose’s criterion 13 ) inducing potential modulations. Furthermore, as demonstrated by the convective nature of this instability, no net damping was observed for the chosen parameters 12 .…”
mentioning
confidence: 99%